Green‐fluorescent proteins in Caribbean corals - Charles H. Mazel; Michael P. Lesser; Maxim Y. Gorbunov; Thomas M. Barry; Julianne H. Farrell; Kevin D. Wyman; Paul G. Falkowski (Limnology and Oceanography, 2003)
Fluorescent pigments in several Indo‐Pacific and Caribbean anthozoans have recently been identified as proteins related to the Green‐fluorescent protein (GFP) of the hydromedusa Aequorea victoria . Here we show that GFP is widely distributed in many Caribbean species. The fluorescence excitation and emission spectra for the pigment are similar to those reported elsewhere for coral and noncoral GFP and the fluorescence quantum yield is estimated to be 35%. Spectral and molecular characterization of the isolated protein clearly show it to be GFP, and laboratory and in situ fluorescence measurements and Western blot analysis show that it is widespread. Bathymetric studies of GFP content using Western blots for the ecologically important congeneric corals Montastraea faveolata and Montastraea cavernosa show that there is no significant correlation between depth and GFP concentration. Nucleotide sequence data of GFP from M. faveolata and M. cavernosa show 88.2% sequence homology with each other and 46.4% homology with A. victoria GFP, whereas the percent homology with A. victoria at the amino acid level was 31.1 and 28.4% for M. cavernosa and M. faveolata , respectively, and 82.7% with each other. Measurements of reflectance and of the excitation spectrum for chlorophyll fluorescence in GFP‐containing corals indicate that GFP absorption, emission, and reflection have negligible impact on the level of solar radiation reaching the zooxanthellae and therefore play no role in coral photosynthesis by either addition or removal of photons.

High‐resolution determination of coral reef bottom cover from multispectral fluorescence laser line scan imagery - Charles H. Mazel; Michael P. Strand; Michael P. Lesser; Michael P. Crosby; Bryan Coles; Andrew J. Nevis (Limnology and Oceanography, 2003)
A prototype in‐water laser line‐scanning multispectral fluorescence imaging system was evaluated for its ability to provide data that could be used to determine the quantitative distribution and abundance of various functional groups on coral reefs. The system collected fluorescence imagery in three spectral bands with 1 cm 2 resolution at sites in Florida and the Bahamas. Fluorescence excitation was at 488 nm, and imagery was collected in emission bands centered at 520, 580, and 685 nm. Ground truth data on bottom cover was collected by divers using conventional line transect and photographic quadrat methods. A set of classification rules based on the relative signal levels in the three fluorescence channels was developed to assign the image pixels to functional groups. Once the image was classified, percent cover data for the groups were computed for the full image and for subsets of the image chosen to simulate line transect, grid survey, and photographic quadrat surveys. The statistics of percent cover of various bottom types derived from the fluorescence image compared favorably with those determined by diver survey techniques. The results demonstrate that fluorescence imaging has the long‐term potential to provide coverage of large spatial areas of coral reefs at high resolution, with automated classification and quantification of functional groups in the image.